NASI BORANAN SEBAGAI DAYA TARIK WISATA KULINER LAMONGAN JAWA TIMUR - Dodik Prakoso Eko Hery Suwandojo (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2020)
Culinary is one of the essential factors of tourism activities including Indonesia Tourism. Lamongan City is also one of the cities that has several types of typical culinary which is an attraction for culinary connoisseurs, especially the local communities or domestic tourists from other cities. This culinary is called Boranan rice or “sego Boranan”, which is authentic and only sold in Lamongan city. Therefore, the potential can be developed, introduced and become a special attraction for the tourists to come over Lamongan. The research method used in this scientific article is a descriptive qualitative research method using data collection techniques namely observation, interview, questionnaire, and documentation. The results of the study revealed that Boranan rice has a pretty good potential to be a culinary tourist attraction for the city of Lamongan. In addition, the promotion carried out by the Lamongan city government through the Lamongan city disparbud has also been done quite well. However, good cooperation is still needed between the government and the sellers of Boranan rice, therefore the marketing and preservation of Boranan rice can run well in the future.Keywords: culinary tourism, destination attraction, east java, boranan rice